PENDAMPINGAN PASTORAL BAGI LANSIA DALAM MENEMUKAN MAKNA HIDUP DI PANTI WERDHA WISMA MULIA - Slamet Riyadi; Yudiahline Ruthasye Sodak (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2026)
This community service activity aims to describe pastoral care for older adults in discovering life meaning at Wisma Mulia Nursing Home. Older adults experience multidimensional changes involving physical, psychological, social, and spiritual aspects, including spousal loss, separation from family, and the need to be heard, valued, and spiritually strengthened. The activity employed a qualitative pastoral care approach through pastoral conversation, in-depth interviews, verbal and nonverbal observation, faith reflection, and prayer. The results indicate that pastoral accompaniment provides a safe space for older adults to reflect on life experiences, process loss, and strengthen spiritual values. The qualitative findings show that life meaning is constructed through honesty, sincerity, faithfulness, acceptance, gratitude, and belief in God’s presence. Empathic relationships between the pastoral caregiver and the older adult also enhance psychospiritual well-being. Therefore, pastoral care plays a significant role in helping older adults live peacefully, meaningfully, and hopefully in later life. ABSTRAKKegiatan Pengabdian kepada Masyarakat ini bertujuan mendeskripsikan pendampingan pastoral bagi lansia dalam menemukan makna hidup di Panti Werdha Wisma Mulia. Lansia menghadapi perubahan fisik, psikologis, sosial, dan spiritual, termasuk kehilangan pasangan, keterpisahan dari keluarga, serta kebutuhan untuk didengarkan dan dikuatkan. Metode kegiatan menggunakan pendekatan pendampingan pastoral kualitatif melalui percakapan pastoral, wawancara mendalam, observasi verbal dan nonverbal, refleksi iman, serta doa. Hasil kegiatan menunjukkan bahwa pendampingan pastoral memberi ruang aman bagi lansia untuk merefleksikan pengalaman hidup, mengolah kehilangan, dan meneguhkan nilai spiritual. Temuan kualitatif memperlihatkan bahwa makna hidup lansia dibangun melalui kejujuran, ketulusan, kesetiaan, penerimaan, syukur, dan keyakinan akan penyertaan Tuhan. Relasi empatik antara pendamping dan lansia juga memperkuat kesejahteraan psikospiritual. Dengan demikian, pendampingan pastoral berperan penting dalam menolong lansia menjalani masa tua secara damai, bermakna, dan penuh pengharapan.